The Unfamiliar Past: The Outreach of Palaeolithic Archaeology in Greek Archaeological Museums - Elefanti, Paraskevi (Ex Novo: Journal of Archaeology, 2021)
The way in which the Stone Age was presented in regional museums in Greece was strongly conditioned by the example set by the National Museum in Athens, with its emphasis on the Classical period after independence from Ottoman rule in 1830. Archaeology and museums provided the ideal tools with which to articulate the links between the emerging nation and perceived past glories. Evidence from earlier periods, being less striking and abundant and more difficult to interpret was side-lined, a pattern which persists today in the relatively small number of museums that devote space to the Palaeolithic and Mesolithic. But this is changing and from the early 2000s onwards in both newly built museums and those that were redeveloped, displays focusing on early prehistory have increased in number. This paper looks at ten such museums and how they present the Palaeolithic and Mesolithic. Despite the increase, the numbers are still too few and the quality of the displays is quite variable, to the extent that the ability of most to engage the public imagination is doubtful.